Modeling and parametric optimization for a solar-powered closed-cycle micro gas turbine for space applications. Issue 1 (February 2021) - Thomas Jayachandran, A V; Tkachenko, A Y; Omar, H H; Krishnakumar, A
Abstract: The research describes the theory design and the modeling of a closed cycle micro gas turbine power plant (CMGTP). A computer simulation model in ASTRA is used to model specifically for this cycle. The software model has been tested for various configurations of gas turbines. For the commercial viability and success of the CMGTP, it should have significant operational feasibility. The working fluid properties play a vital role. The research is a feasibility study to examine the technology for Brayton-cycle based solar thermal power plants and to optimize the model in comparison with Solar array photovoltaic cells to increase the power density by increasing the power generated per unit solar-collector area. A mathematical model for CMGTP was de-signed to power satellites in space environments. The goal is to provide electricity from a parabolic mirror acting as a heat source that is collected by pointing at the sun. The Closed Brayton Cycle power was simulated to produce an output of 6 kW at the generator terminal. The heat source generated from the sun was considered to be around 750 K to 1250 K. The vacuum at the space radiation environment was considered to be 200 K acting as a coolant sink. The optimization of the power plant priorities is followed as High thermal-to-electric efficiency, Low mass, and volume. Computer simulation for thermodynamic analysis was performed on the selection of the working fluids, Brayton cycle design parameters, a heat exchanger (heating and cooling temperatures) that meets the best criteria. A system-level tradeoff study was performed to optimize for achieving target functions for critical factors. The CMGTP consists of a centrifugal compressor, a radial in-flow turbine on a single shaft powering a two-pole permanent magnet alternator.